URANIUM-SERIES DATING APPLICATIONS IN NATURAL ENVIRONMENTAL SCIENCE - van Calsteren P.V.C.; Thomas L. (My University, 2006)
Uranium-series (U-series) analyses are an essential component of many research projects in Earth and environmental science, oceanography, hydrology and science-based archaeology. Topics range from magma chamber evolution and volcanic hazard prediction, global climatic change through dating of authigenic carbonate deposits, human evolution through dating of bone, to the study of groundwater evolution. The U-series decay chains contain many elements that can be fractionated in environmental and geological processes. Half-lives of radioactive isotopes of such elements range from seconds to many millennia and application depends on the natural timeframe of the process or the elapsed time. This review will be limited to some aspects of the 238 U- 234 U- 230 Th- 226 Ra system with half-lives of 245 kyr, 76 kyr and 1.6 kyr, respectively. In environmental systems, fractionation of uranium and thorium is a very efficient process because thorium is extremely insoluble while hexavalent uranium in oxidising conditions is relatively soluble. Many authigenic precipitates of calcite contain virtually no thorium and inorganic precipitates have U/Ca ratios very similar to the ratio of dissolved uranium and calcium. Almost no radiogenic 230 Th in the precipitate means that the radiogenic clock starts effectively at zero. However, pure authigenic precipitates are rare and many contain some allogenic material, mostly silicate with 238 U in secular equilibrium with significant 230 Th. Some of the characteristics of different types of samples and various methods to accommodate or correct for 'inherited' 230 Th will be discussed. Authigenic material should remain a 'closed system' with respect to the relevant isotopes but that requirement is sometimes difficult to maintain because radioactive decay results in damage to the crystal lattice of the host mineral. Consequences of this 'recoil effect' and correction schemes will be discussed. Dating archaeological bone based on the systematics of diffusion and adsorption to effectively model 'open system' behaviour is also included. © 2005 Elsevier B.V. All rights reserved.
Keywords: ALLOGENIC; AUTHIGENIC; DATING; ENVIRONMENT; OPEN-SYSTEM; URANIUM-SERIES DISEQUILIBRIUM